Approximately $ 31419 profit is earned from selling books in entire month
Solution:
Given that Jodie had sold 885 copies of her new book
At the end of the month, she had sold 1,364 copies of her book
We have to determine the profit earned in the entire month
From given information,
Start of month sale = 885 copies
End of month sale = 1364 copies
Total copies of books sold = Start of month sold + end of month sold
Total copies of books sold = 885 + 1364 = 2249
Also given that each book profit is $ 13.97
Profit of 1 book = $ 13.97
Therefore for 2249 books, profit earned is given as:
Profit of 2249 books = $ 13.97 x 2249 = 31418.53
Therefore approximately $ 31419 profit is earned from selling books in entire month
Which of the following are NOT vector directions?
A. 35 degrees north of east
B. north
C. outside 45 degrees
D. 35 degrees inside
Final answer:
The correct answer is C. outside 45 degrees. In this question, we are asked to identify which directions are NOT vector directions. Options A, B, and D all describe vector directions, but option C does not.
Explanation:
The correct answer is C. outside 45 degrees.
In this question, we are asked to identify which directions are NOT vector directions. A vector direction is a specific direction or angle that describes the orientation of a vector.
Options A, B, and D all describe vector directions:
A. 35 degrees north of east: This describes a vector direction that is 35 degrees north of the east direction.
B. north: This is a vector direction that points directly north.
D. 35 degrees inside: This describes a vector direction that is 35 degrees inside the reference angle.
Option C, outside 45 degrees, does not describe a specific vector direction. It is not clear whether the direction is outside 45 degrees to the left or right. Therefore, option C is NOT a vector direction.
4 - (-8) =
What is the answer
Answer:
12
Step-by-step explanation:
When you subtract a negative number, the two negatives make a plus sign.
4 - (-8)
= 4 + 8
= 12
How do you find the least common multiple or the lcm of 10 and 8
Answer:
40
Step-by-step explanation:
Least common multiple (lcm) = the smallest multiple that both numbers have.
Let's figure it out.
10 = 2 x 5
8 = 2 x 2 x 2
the ones I have highlighted, we will multiply them all together, except for a 2.
we didn't multiply one of the 2's because they both have a two, so we only keep one of them.
so it is 2 x 5 x 2 x 2
let me say it again, because they both share a same 2, that one is eliminated.
so the answer is 40 because:
2 x 5 x 2 x 2
= 10 x 4
= 40
Answer:
Step-by-step explanation:
list the multiples of 8 and 10 and mark wich one is the lowest number
What is 2y=4x-2/5 in standard form
Answer:
4x-2y=2/5
Step-by-step explanation:
2y=4x-2/5
4x-2y=2/5
1) Luis uses 1.6 liters of gasoline each hour he
spends mowing lawns. How much gas does he
use in 5.8 hours?
Answer:
9.28 Liters
Step-by-step explanation:
All we have to do is multiply the time by amount her time unit.
Degrees Celsius can be converted to degrees Fahrenheit by multiplying 1 and 4/5 and adding 32 degrees C what is 15 degrees C in Fahrenheit
Answer:
15C is 59F
Step-by-step explanation:
As an equation, F = (1 4/5)C + 32. 1 and 4/5 is the same as 9/5.
Substitute 15 for C.
F = (9/5)C + 32
F = (9/5)(15) + 32 Multiply 15 by the top number in 9/5
F = 135/5 + 32 Convert 32 to a fraction over 5
F = 135/5 + 160/5 Add the numerators under the same denominator
F = 295/5 Divide
F = 59 Degrees in Farenheit
Therefore 15°C is 59°F.
What is the remainder of 428/19. I know it equals 22, but what’s the remainder
Answer:
the remainder is 10
Step-by-step explanation:
Answer:
R=10
Step-by-step explanation:
1. 428/19=22
2. R=10
Steps for checking your work:
1. Multiply the divisor by the answer (aka quotient)
2. After that, add the remainder to the answer you got from doing step 1 for checking your work (aka proudct, since you multiplied)
f h(x) = 6 – x, what is the value of (h circle h) (10)?
Answer:
Step-by-step explanation: when h(x) = 10
h(x)= 6-x
h(10)= 6-10
=-4
If you deposit $1,000 in an account that pays 6% annual interest compounded
continuously, what will the balance be after five years?
Answer:
I think it's $1,349.86
Answer:
It's $1,349.86
Step-by-step explanation:
(trust me bro)
what is the distance between the y-intercept and the x-intercept of the line whose equation is y=3x+12
The distance between the y-intercept and the x-intercept of the line is 12.64911 units or [tex]\sqrt{160}[/tex] units
Solution:
Given equation is y = 3x + 12
We have to find the distance between y-intercept and the x-intercept of the line whose equation is y = 3x + 12
Let us first find the x - intercept and y - intercept
The x-intercept is the point at which the line crosses the x-axis. At this point, the y-coordinate is zero.
The y-intercept is the point at which the line crosses the y-axis. At this point, the x-coordinate is zero
Finding x - intercept:
To find the x-intercept of a given linear equation, plug in 0 for 'y' and solve for 'x'.
Substitute y = 0 in given equation
y = 3x + 12
0 = 3x + 12
3x = -12
x = -4
Thus the x - intercept is (-4, 0)
Finding y - intercept:
To find the y-intercept, plug 0 in for 'x' and solve for 'y'
Substitute x = 0 in given equation
y = 3x + 12
y = 3(0) + 12
y = 12
Thus the y - intercept is (0, 12)
Now let us find the distance between x intercept and y intercept
Distance between two points [tex]P(x_1, y_1) \text{ and } Q(x_2, y_2)[/tex] is given by:
[tex]d=\sqrt{\left(x_{2}-x_{1}\right)^{2}+\left(y_{2}-y_{1}\right)^{2}}[/tex]
Here the distance between (-4, 0) and (0, 12) is given as:
[tex]\begin{aligned}&d=\sqrt{(0-(-4))^{2}+(12-0)^{2}}\\\\&d=\sqrt{4^{2}+12^{2}}\\\\&d=\sqrt{16+144}=\sqrt{160}\\\\&d=12.64911\end{aligned}[/tex]
Thus the distance between the y-intercept and the x-intercept of the line is 12.64911 units or [tex]\sqrt{160}[/tex] units
The y-intercept of the line y=3x+12 is (0,12) and the x-intercept is (-4,0). The distance between these two points is approximately 12.65 units.
Explanation:The equation given is y=3x+12. The x-intercept is the point where the line crosses the x-axis (where y=0), and the y-intercept is where the line crosses the y-axis (where x=0).
For the y-intercept, we simply replace x with 0, so y = 3(0) + 12 = 12. Thus, the y-intercept is (0,12).
For the x-intercept, we replace y with 0, so 0 = 3x + 12. Solving this equation for x gives x = -4. Thus, the x-intercept is (-4,0).
The distance between two points in the coordinate plane is given by the formula √[(x2-x1)² + (y2-y1)²]. Therefore, the distance between the x-intercept and the y-intercept is √[(-4-0)² + (0-12)²] = √(16 + 144) = √160 = 12.65.
Learn more about distance between intercepts here:https://brainly.com/question/36510812
#SPJ3
A garden centre has reduced the price of all plant pots by 20%. Jane bought a reduced plant pot for £40. How much would she have paid for this plant pot before the price reduction?
She paid 80% of the regular price because it was 20% off so...
80% = £40
We want to get to the regular price (100%) so...
100% = £40 x 100/80 = £50
answer: £50
Answer:he paid 80% of the regular price because it was 20% off so...
80% = £40
We want to get to the regular price (100%) so...
100% = £40 x 100/80 = £50
answer: £50
Step-by-step explanation:
The isosceles trapezoid is part of an
isosceles triangle with a 46° vertex angle.
Enter the measure of an acute base angle of
the trapezoid.
Final answer:
Using the properties of isosceles triangles, the acute base angle of the isosceles trapezoid, which is part of an isosceles triangle with a 46° vertex angle, is found to be 67°.
Explanation:
To find the measure of an acute base angle of the isosceles trapezoid that is part of an isosceles triangle with a 46° vertex angle, we can apply the properties of isosceles triangles. By the Isosceles Triangle Theorem, we know that the angles opposite the equal sides are equal.
Since the given triangle is isosceles, the two base angles must also be equal. Additionally, we know that the sum of all angles in any triangle is 180°.
Let's call each of the base angles B. Then, the sum of all angles in the triangle is:
46° + B + B = 180°
Now we solve for B:
2B = 180° - 46° = 134°
B = 134° / 2 = 67°
Thus, each base angle of the isosceles triangle is 67°. Next, considering the isosceles trapezoid, we know the adjacent angles must be supplementary because they are on the same line. This means that one base angle of the isosceles trapezoid equals:
180° - 67° = 113°
However, since the student is looking for the measure of an acute base angle of the trapezoid and 113° is an obtuse angle, the acute base angle is the original 67° angle that we found. This is because the acute and obtuse angles in the trapezoid are adjacent angles around the same vertex, and the acute angle is the angle that's interior to the triangle.
Therefore, the measure of an acute base angle of the trapezoid is 67°.
5) Linda picked a basket of apples. She gave half of the apples to a neighbor, then 10 apples to her mother, then half of the remaining apples to her best friend, and she kept the remaining 3 apples for herself. How many apples did she start with in the basket?
I need help this is due this Wednesday on my college math class! ASAP!!! This needs to be shown full work for full credit!!
Answer:
is it 8 apples to her mother or 10 since I had this exact problem?
Step-by-step explanation:
Ashe started with 32 apples in the basket initially.
How to find half of something ?To find the half of something just multiply 1/2 with the given value.
According to the given question Linda picked a basket of apples.
Assuming she had x apples initially.
She gave half of the apples to the neighbour,Therefore she now has (x - 1/2x) apples which is = 1/2x apples.
Then she gave 10 to her mother,So the remaining apples she has now is
= ( 1/2x - 10 ) apples
= (x - 20)/2.
Then she gave half of the apples to her best friend so the no. of apples she has now is (x - 20)/2×1/2 which is = (x - 20)/4 and she kept the remaining 3.
∴ (x - 20)/4 = 3
x - 20 = 12
x =32.
learn more about these type of problems here :
https://brainly.com/question/24232390
#SPJ2
Zachary can spend no more than $94 per day to rent a car. A car rents for $30 per day plus $0.20 per mile. Write an inequality for this situation. Graph the solutions on a number line. What does the graph show
Answer:
$124.20 miles all you gotta do is add them together
Step-by-step explanation:
12-2/3x=x-18 so how do you answer this question
Answer:
Step-by-step explanation:
I think I've already answered this question.
what is the distance from 10 To 0
Answer:
10
Hope this helps :)
Answer:
rthw aeenser is 20
Step-by-step explanation:
If x+y=11 and xy=15, find the value of x^2 + y^2
There is actually some tactics to this. I tried to find x and y first but they are very messy numbers but...
We know...
(x+y)²=x²+2xy+y²
In this case, (x+y)² = 11² = 121.
So, x²+2xy+y²=121
We also know that xy=15 and furthermore that 2xy=30.
x²+y² = 121-30 = 91
answer: 91
The value of x^2 + y^2 is 91.
To find the value of x^2 + y^2 given that x+y=11 and xy=15, we can use algebraic identities. We will use the fact that (x+y)^2 = x^2 + 2xy + y^2. We know that x+y=11, so (x+y)^2 = 11^2 = 121. Also given is xy=15, which we'll use in the identity mentioned.
Now, let's substitute the values into the identity:
(x+y)^2 = x^2 + 2xy + y^2
121 = x^2 + 2(15) + y^2
121 = x^2 + 30 + y^2
121 - 30 = x^2 + y^2
91 = x^2 + y^2
(10x - 17)
(6y + 29)\(8x + 1)
the product of (10x - 17) and (6y + 29)(8x + 1) is:
[tex]\[ 480xy^2 - 756xy + 2320x^2 - 3654x - 102y - 493 \][/tex]
you want to multiply the expressions (10x - 17) and (6y + 29)(8x + 1). Let's proceed with the multiplication:
First, distribute (6y + 29) into (8x + 1):
[tex]\[ (6y + 29)(8x + 1) = 6y \cdot 8x + 6y \cdot 1 + 29 \cdot 8x + 29 \cdot 1 \]\[ = 48xy + 6y + 232x + 29 \][/tex]
Now, multiply the result by (10x - 17):
[tex]\[ (10x - 17)(48xy + 6y + 232x + 29) \]\[ = 10x \cdot (48xy + 6y + 232x + 29) - 17 \cdot (48xy + 6y + 232x + 29) \]\[ = 480xy^2 + 60xy + 2320x^2 + 290x - 816xy - 102y - 3944x - 493 \]\[ = 480xy^2 - 756xy + 2320x^2 - 3654x - 102y - 493 \][/tex]
So, the product of (10x - 17) and (6y + 29)(8x + 1) is:
[tex]\[ 480xy^2 - 756xy + 2320x^2 - 3654x - 102y - 493 \][/tex]
The probable question maybe:
multiply the expressions (10x - 17) and (6y + 29)(8x + 1).
The product of (10x - 17) and (6y + 29)(8x + 1) is: = [tex]\[ 480xy^2 - 756xy + 2320x^2 - 3654x - 102y - 493 \][/tex]
You have to multiply the expressions (10x - 17) and (6y + 29)(8x + 1). Let's proceed with the multiplication:
First, distribute (6y + 29) into (8x + 1):
[tex]\[ (6y + 29)(8x + 1) = 6y \cdot 8x + 6y \cdot 1 + 29 \cdot 8x + 29 \cdot 1 \]\[[/tex]
= 48xy + 6y + 232x + 29
Now, multiply the result by (10x - 17):
[tex]\[ (10x - 17)(48xy + 6y + 232x + 29) \]\\\\ = 10x \cdot (48xy + 6y + 232x + 29) - 17 \cdot (48xy + 6y + 232x + 29) \]\\\\ = 480xy^2 + 60xy + 2320x^2 + 290x - 816xy - 102y - 3944x - 493 \]\\\\ = 480xy^2 - 756xy + 2320x^2 - 3654x - 102y - 493 \][/tex]
So, the product of (10x - 17) and (6y + 29)(8x + 1) is:
[tex]\[ 480xy^2 - 756xy + 2320x^2 - 3654x - 102y - 493 \][/tex]
The complete question is:
Multiply the expressions (10x - 17) and (6y + 29)(8x + 1).
Beverley is buying hot dogs and hot dog buns for a picnic. She wants to buy one got dog for each bun with none left over. The hot dogs come packed 12 in a package. The buns come packed 8 in a package. What is the least amount of each beverly needs to buy? How many packages of each item would she buy?
Answer:
Number of hot dog packets = [tex]\frac{24}{12}[/tex] = 2
Number of bun packets = [tex]\frac{24}{8}[/tex] = 3
Step-by-step explanation:
Beverley is buying hot dogs and hot dog buns for a picnic. She wants to buy one got dog for each bun with none left over. The hot dogs come packed 12 in a package. The buns come packed 8 in a package.
We have to find the lowest common multiple of 8 and 12 and from observation we can see that it is 24.
So Beverly would have to buy around 24 pieces of hot dogs and buns.
Number of hot dog packets = [tex]\frac{24}{12}[/tex] = 2
Number of bun packets = [tex]\frac{24}{8}[/tex] = 3
Answer:
Beverly would have to buy around 24 pieces of hot dogs and buns.
Step-by-step explanation:
same hope this help
If value of x is 5, help me solve the area of this geometry figure :)
Answer:
102
Step-by-step explanation:
X=5 so from A to E is 5. 5 squared is 25 plus 4 = 29 then add 29 to 5 you get 34. Then multiply 34 times 6 you get 204 then divide by 2 because area of triangle is base times height divided by 2 you get 102.
The expression above should be further simplified for which value of x?
Sq rt 215x
A) 35
B) 118
C) 34
D) 7
The expression √215x should be further simplified for (a) 35 as the value of x
How to determine the value of x
From the question, we have the following parameters that can be used in our computation:
√215x
Taking each value of x from the list of options, we have
√215x = √(215 * 35)
Expanding, we get
√215x = √(5 * 43 * 7 * 5)
This gives
√215x = 5√301
Next, we have
√215x = √(215 * 118)
Expanding, we get
√215x = √(5 * 43 * 2 * 59)
This gives
√215x = √(25370)
Next, we have
√215x = √(215 * 34)
Expanding, we get
√215x = √(5 * 43 * 2 * 17)
This gives
√215x = √7310
Next, we have
√215x = √(215 * 7)
Expanding, we get
√215x = √(5 * 43 * 7)
This gives
√215x = √1505
Hence, the value of x is 35
Which of the following systems of inequalities has Point C as a solution?
A:
[tex]f(x)\leq 3x+4\\g(x)\leq -\frac{1}{2} x-5\\[/tex]
B:
[tex]f(x)\geq 3x+4\\g(x)\leq -\frac{1}{2} x-5[/tex]
C:
f(x) ≤ 3x + 4
[tex]g(x)\geq -\frac{1}{2}x-5[/tex]
D:
f(x) ≥ 3x + 4
[tex]g(x)\geq -\frac{1}{2} x-5[/tex]
Answer:
Option A.
[tex]f(x)\leq 3x+4[/tex]
[tex]g(x) \leq-\frac{1}{2}x-5[/tex]
Step-by-step explanation:
we know that
If point C is a solution of the system of inequalities, then point C must satisfy both inequalities
Point C is located below the solid line f(x) and below the solid line g(x)
so
The shaded region of the solution set of the system must be below of the inequality f(x) and must be below of the inequality g(x)
therefore
The system is
[tex]f(x)\leq 3x+4[/tex]
[tex]g(x) \leq-\frac{1}{2}x-5[/tex]
Answer:
B
Step-by-step explanation:
Ollie used 852 heads to make 4 bracelets he put the same number of beads on each bracelet how many beads does each bracelet have
Answer: 213
Step-by-step explanation:
852/4 = 213
Answer:
213
Step-by-step explanation:
852/4 = 213
He is splitting 852 beads into 4 bracelets (groups)
What type of dilation is described with equation below
Contraction. It gets smaller as the image is shrunk. It will be a fraction of the original triangle.
⭐ Please consider brainliest! ⭐
✉️ If any further questions, inbox me! ✉️
If g = 3, evaluate (solve) the following expression. 2g + 7= _____
Answer:
13.
Step-by-step explanation:
2g + 7
= 2(3) + 7
= 6 + 7
= 13.
Answer: 13
Step-by-step explanation: In this problem, we have the xpression 2g + 7 and we want to evaluate the expression when g is equal to 3.
To evaluate an expression, we simply plug the value of the variable into the expression and solve. So here, since g is equal to 3, we have 2 (3) + 7. 2 × 3 is equal to 6 so we have 6 + 7 which is equal to 13.
So the value of our expression when g is equal to 3 is 13.
Remember, when we see a variable like g next to a number, it means multiplication so you want to multiply by the value of the variable.
Find x, y and z for the following triangle.
Please show the steps with details, Thanks!
Answer:
x = 100°
y = 125°
z = 55°
Step-by-step explanation:
A straight line is 180°
A triangle is 180°
Solve in this order:
X: 180 - 80 = 100
Z: 180 - 80 - 45 = 55
Y: 180 - 55 = 125
The table shows the average cost, in dollars, of a movie ticket in the United States for different years. Calculate the correlation coefficient. Round to the nearest hundredth.
Year Cost
1948 0.36
1963 0.86
1974 1.89
1978 2.34
1985 3.55
1991 4.21
1997 4.59
2005 6.41
2010 7.89
0.12
0.96
0.93
1
Answer:
The correlation coefficient is 0.96
Step-by-step explanation:
The Given Table showing year and cost:
Year Cost
1948 0.36
1963 0.86
1974 1.89
1978 2.34
1985 3.55
1991 4.21
1997 4.59
2005 6.41
2010 7.89
Regression table:
Regression table can be made if we rewrite the year column by associating
1948 with 0, and the years after 1948 to be associated with the number of years after 1948. For example, if 1948 is associated with 0, then 1963 would come after 15 years, hence 1963 would be represented by 15, and with the same way, we can associate other years as well. Have a look:
Year (X) Cost (Y) X² XY
0 0.36 0 0
15 0.86 225 12.9
26 1.89 676 49.14
30 2.34 900 70.2
37 3.55 1369 131.35
43 4.21 1849 181.03
49 4.59 2401 224.91
57 6.41 3249 365.37
62 7.89 3844 489.18
∑X= 319 ∑Y= 32.1 ∑X²= 14513 ∑XY= 1524.08
As the correlation coefficient (r) can be determined as follows:
r = n (∑ XY) - (∑X) (∑Y) ÷ √[n(∑X²)-(∑Y)²][n(∑Y²)-(∑Y)²]
But, we need an additional column Y²
So,
Y²
0.1296
0.7396
3.5721
5.4756
12.6025
17.7241
21.0681
41.0881
62.2521
∑Y² = 164.6518
As,
r = n (∑ XY) - (∑X) (∑Y) ÷ √[n(∑X²)-(∑Y)²][n(∑Y²)-(∑Y)²]
So,
r = 9 (524.08) - (319)(32.1) ÷ √[9(14513 )-(319)²][9(164.6518)-(32.1)²]
[tex]r = \frac{3476.82}{\sqrt{(28856)(451.4562)}}[/tex]
[tex]r = \frac{3476.82}{\sqrt{(13027220.11)}}[/tex]
[tex]r = \frac{3476.82}{\sqrt{(3609.32)}} = 0.96[/tex]
So, the correlation coefficient is 0.96.
Keywords: correlation coefficient
Learn more correlation coefficient from brainly.com/question/3900657
#learnwithBrainly
Simon took out an unsubsidized student loan of $43,000 at a 2.4% APR,
compounded monthly, to pay for his last six semesters of college. If he will
begin paying off the loan in 33 months with monthly payments lasting for 20
years, what will be the amount of his monthly payment?
The amount of Simon's monthly payment, rounded to the nearest cent, is approximately $240.17.
To calculate the monthly payment for Simon's loan, we need to use the formula for an annuity, which is derived from the amortization formula for loans. The formula to find the monthly payment (M) is:
[tex]\[ M = \frac{P \times r \times (1 + r)^n}{(1 + r)^n - 1} \][/tex]
where:
- [tex]\( P \)[/tex] is the principal amount of the loan ($43,000)
- [tex]\( r \)[/tex] is the monthly interest rate (APR divided by 12)
- [tex]\( n \)[/tex] is the total number of payments (20 years times 12 months per year)
First, we need to convert the annual percentage rate (APR) to a monthly interest rate by dividing by 12:
[tex]\[ r = \frac{2.4\%}{12} = \frac{0.024}{12} = 0.002 \][/tex]
Next, we calculate the total number of payments:
[tex]\[ n = 20 \text{ years} \times 12 \text{ months/year} = 240 \text{ months} \][/tex]
Now we can plug these values into the formula:
[tex]\[ M = \frac{43000 \times 0.002 \times (1 + 0.002)^{240}}{(1 + 0.002)^{240} - 1} \][/tex]
[tex]\[ M = \frac{43000 \times 0.002 \times (1.002)^{240}}{(1.002)^{240} - 1} \][/tex]
Using a calculator, we find:
[tex]\[ (1.002)^{240} \approx 1.558 \][/tex]
Now we can calculate the monthly payment:
[tex]\[ M = \frac{43000 \times 0.002 \times 1.558}{1.558 - 1} \][/tex]
[tex]\[ M = \frac{43000 \times 0.002 \times 1.558}{0.558} \][/tex]
[tex]\[ M = \frac{134.034}{0.558} \][/tex]
[tex]\[ M \approx 240.17 \][/tex]
Therefore, the amount of Simon's monthly payment, rounded to the nearest cent, is approximately $240.17.
Answer:
241.16
Step-by-step explanation:
Subtract the following.Write your answer in standard notation. 15 - 1.3 * 10^-3
Answer:
The Final Answer would be 14.9987.
Step-by-step explanation:
Given:
[tex]15-1.3\times 10^-3[/tex]
We need to Subtract the above number.
Since the larger number is standard Notation form and smaller number is in Scientific notation form
So first we will convert the Scientific notation Number in standard Notation form we get;
[tex]1.3\times 10^-3 = 0.0013[/tex]
Now Subtracting the smaller Number from larger number we get;
[tex]15-0.0013 = 14.9987[/tex]
Hence The Final Answer would be 14.9987.
Which choice is the most efficient first step to solve this set of equations?
Answer:
Option b) is correct
3x+4(2x+4)=17 Substitute (2x+4) for y in the second equation
Step-by-step explanation:
Given Equations are
[tex]y=2x+4\hfill (1)[/tex] and [tex]3x+4y=17\hfill (2)[/tex]
To solve the given equations we have to find the value of
x and y values.
Here y value is given so that we can substitute y=3x+4 value in second equation
ie., Substitute equation (1) in (2) equation we can easily get x value.
Therefore substitute (2x+4) for y in the second equation we get
3x+4(2x+4)=17
Option b) is correct